[ETS POSES GREATER THREAT THAN ANY OTHER SINGLE TOBACCO ISSUE] - KLOEPFER W (Tufts Archival Research Center, 2007)
Memo / cover letter for first draft of the Tobacco Institute’s Environmental Tobacco Smoke (ETS) program. Asserts that ETS is the most threatening tobacco issue. Reflects the need for a comprehensive program to handle ETS. Requests criticism and comments on the proposed draft.